PENERAPAN METODE RELAKSASI BENSON PADA LANSIA PEREMPUAN DENGAN HIPERTENSI: PENERAPAN METODE RELAKSASI BENSON PADA LANSIA PEREMPUAN DENGAN HIPERTENSI - Rini Widarti; Hermawati (P3M Universitas Aisyiyah Surakarta, 2023)
The elderly is the final stage of the life cycle, and degenerative processes occur in various aspects, which result in a greater risk of exposure to diseases such as hypertension which is usually often found in the elderly. Women are closely related to the occurrence of hypertension when experiencing menopause. Menopausal women experience decreased estrogen, which protects blood vessels from damage. One of the things that can be done to keep blood pressure stable is to use Benson relaxation, which is the development of a relaxation response method involving the belief factor to achieve optimal health conditions. The number of elderly who participated in this training was 17 people. Before the training and presentation of the material, data was obtained that 3 elderly people knew the benefits of Benson relaxation, and 14 people did not know about it. After the training, it was found that 10 elderly people understood Benson relaxation, and 7 other people did not understand this, which means that there was an increase in the understanding of the elderly about the benefits of Benson relaxation in hypertension. Keywords: elderly; hypertension; relaxation management